A Comprehensive History of India : (Vol. IV, Part 2) - Sharma, R.S.; Shrimali, K.M. (Brill | Manohar Publishers & Distributors, 2023)
The Fourth Volume of A Comprehensive History of India covers the period from c. 985 CE to 1206 CE. A clear and connected source-based account of the political organization of this period has been provided by competent contributors in the first part of the volume published a few years ago. The second part of the volume being presented here, treats social, economic, religious, literary and cultural developments together with coinage, science and technology and India's contacts with the outside world during the period. All contributions are marked by their varied perspectives taking cognisance of not only regional specificities, but also of the macro-view of such developments. Notwithstanding the multiplication of political power centres during the period under survey, the dynamism of socio-economic and cultural lives of people never faded away. The volume locates this dynamism within the broad pan-India vision. It also includes more than a hundred illustrations, is provided with an exhaustive and up to date bibliographic survey and multi-faceted index to facilitate location of reader's curiosities.